FROM LANDSCAPE TO BRANDSCAPE: THE ROLE OF LOCAL CULTURAL IDENTITY IN SHAPING GUILIN’S TOURISM BRAND PERCEPTION - Huang, Xi; Tengku Anuar , Tengku Fauzan (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This article takes the tourism brand of Guilin as the research object to explore how the local cultural identity shapes tourists' brand perception in the transformation process from "landscape" to "brand landscape". Through qualitative research and questionnaire surveys, this paper analyzes how the natural landscapes and distinctive cultural resources of Guilin are refined into symbolic and differentiated brand elements, and examines tourists' cognition and emotional connection to these elements. Research has found that embedding local cultural identity into tourism brands through narrative construction, visual symbols and experience design can not only enhance brand uniqueness, but also stimulate tourists' cultural identity and sense of belonging, thereby improving brand loyalty. The research provides theoretical inspiration for the branding of destinations in the context of the integration of culture and tourism, emphasizing the core role of cultural roots in the long-term competitiveness of brands.